PROPAGANDA JEPANG: BENTUK SASTRA DALAM MAJALAH SOEARA MOESLIMIN INDONESIA DAN DJAWA BAROE - agustin, sheilla kartika (Program Studi Pendidikan Sejarah - Universitas Samudra, 2022)
Abstract In Japan's attempt to build an empire in Asia, Japan has waged a pacific war. In planning their move to the south, the Japanese also invaded Indonesia, which began with air raids, and was followed by troop landings. After that Japan managed to control various areas in Indonesia. In addition, Japan carried out a propaganda campaign in Indonesia in which the propaganda itself was a series of messages that sought to influence the opinions and behavior of a community or group of people. Where there are various kinds of media used by Japan as a propaganda tool, one of which is magazines. There are various kinds of magazines or newspapers such as Soeara Moeslimin Indonesia magazine and also Djawa Baroe. Soera Moeslimin Indonesia magazine is a printed Islamic magazine and is also published by an Islamic organization Masyumi. Where in the media this magazine contains various kinds or various propaganda content such as the spirit of working for Japan (Romusha) so that this makes people work for Jeepang, besides that they also learn Japanese, and the spirit to follow the military where it is all done for the indigenous people or the people. Indonesia wanted to help Japan in the war in the pacific instead of getting independence. By using the historical research writing method, at the beginning of the activity, it was collected various sources related to the discussion, namely Japanese propaganda in Soeara Moeslimin Indonesia magazine and also Djawa Baroe. Sources that can be used are books, journals, document archives, or thesis. After the sources are obtained, the various sources are arranged in order to facilitate the interpretation of a historical source. And then look for linkages from these sources. At the last stage, namely historiography, the writing of history which will be the result of the reconstruction of various kinds of historical facts that exist in accordance with the theme of writing. Keywords: Propaganda, japan, Magazine